DEVELOPMENT OF AUTOMATIC IRRIGATION SYSTEM WITH SOLAR ENERGY-BASED TELEGRAM NOTIFICATION - Suhardi Rahman, Edi; Fajryanisari , Indah (Fakultas Teknik Universitas Negeri Makassar, 2023)
This study aims to produce an irrigation system development product using Wemos D1 as an irrigation control system, monitoring the state of soil moisture in stages and the state of the water pump by sending data periodically through the Telegram Messenger application. The research was conducted using the R&D (Research and Development) method and the prototype development model. The development procedure includes the stages of needs analysis, system design and design, making system prototypes, testing and validation stages. The results of the Black Box test obtained a percentage of 100% indicating that the prototype was feasible to use. Testing the working system of the tool where on the results of Testing Tool Conditions the Water Pump can work well, the Capacitive Soil Moisture Sensor can detect dry soil moisture when <20% and the soil is wet> 20%, and the HC-SR04 Ultrasonic Sensor test can be used from 2 cm up to 22 cm as a reading of the tank contents. The results of testing user satisfaction with 20 respondents obtained a percentage of 90% in the very good category and 10% in the good category.